The Role of Religious Groups and Small and Medium Enterprises in The Mining Sector After The Amendment of The Mineral And Coal Law in 2025 - Margono, Bagus; Inayah, Nurul (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Amendments to the Mineral and Coal Law (UU Minerba) 2025 provide priority access to religious organizations and small and medium enterprises (UKM) in the mining sector. This policy aims to increase community economic participation and encourage equal distribution of welfare. This research uses a qualitative method with a literature study approach to analyze the implications of this policy. The results of the study show that religious groups have the potential for community-based economic empowerment, workforce education, and the application of ethical principles in mine management. SMEs, on the other hand, can contribute to the diversification of the local economy, although they face challenges in terms of capital and technology. This amendment also has broad socio-economic impacts, including the potential to increase community welfare, the risk of conflicts of interest, and environmental challenges. Therefore, clear regulations and assistance programs are needed to ensure the implementation of this policy is effective and sustainable.